2023
DOI: 10.1093/ecco-jcc/jjac190.0963
|View full text |Cite
|
Sign up to set email alerts
|

P833 Cervical cancer risk in newly diagnosed ulcerative colitis: a nationwide population-based study

Abstract: Background The association between ulcerative colitis (UC) and increased risk of cervical cancer in women remains controversial. We investigated cervical cancer risk in South Korean UC patients using the Korean National Health Insurance (NHI) claims data. Methods UC definitions included both ICD-10 codes and UC-specific prescriptions. We analyzed incident cases diagnosed between 2006 and 2015. Age-matched women without UC (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cases of PC19-PF have increasingly been reported in the literature from about two years since the onset of COVID-19, although CT scan evidence of lung fibrosis may appear much earlier in some patients [17]. A population-based study in Korea demonstrated that vaccination against COVID-19 decreased the incidence of post-COVID-19 interstitial lung disease (which includes PC19-PF), i.e., an incidence of 0.8 vs. 1.83 per 1000 person-years between the vaccination cohort and the controls, respectively [18]. Despite our patient being on pirfenidone 250 mg thrice daily since August 2022 (when the pulmonary fibrosis was first demonstrated on a CT scan), she has had progressive worsening of the pulmonary fibrosis until she's currently oxygen-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of PC19-PF have increasingly been reported in the literature from about two years since the onset of COVID-19, although CT scan evidence of lung fibrosis may appear much earlier in some patients [17]. A population-based study in Korea demonstrated that vaccination against COVID-19 decreased the incidence of post-COVID-19 interstitial lung disease (which includes PC19-PF), i.e., an incidence of 0.8 vs. 1.83 per 1000 person-years between the vaccination cohort and the controls, respectively [18]. Despite our patient being on pirfenidone 250 mg thrice daily since August 2022 (when the pulmonary fibrosis was first demonstrated on a CT scan), she has had progressive worsening of the pulmonary fibrosis until she's currently oxygen-dependent.…”
Section: Discussionmentioning
confidence: 99%